PEREMPUAN DI TIMUR TENGAH DAN AFRIKA UTARA: ETNOGRAFI PERILAKU DAN PENGENDALIAN SEKSUAL - Isfironi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
Scholarly approaches to understanding modesty and sexual restraint in Islamic cultures in the Middle East and North Africa are increasingly nuanced and sensitive, privileging the view of these issues from the perspective of those who practice them. Such perspectives are complex, ever-changing, and shaped by a variety of forces, including most centrally an individual’s sense of self, religious understanding, and historical context. Stephens’ (1972) argument concerning the association of the most elaborate modesty practices with preindustrial societies is to some extent borne out here. Indeed, the ethnographic examples discussed here are drawn primarily from peasant societies that are not industrialized (although other areas in their countries may be)— societies in which Islam plays a major role, and there are premarital and extramarital sex restrictions. Yet this argument cannot effectively explain why, for example, urban educated working women in Cairo are adopting the veil in increasing numbers (Macleod, 1991), or the growing appeal of Orthodox Jewish practices and their accompanying modesty practices for women (Kaufman, 1989). It remainsto be seen what, if any, generalizations can be drawn from the resurgence of modesty practices among particular segments of urban educated women in varying parts of the world.